An interim analysis of a gestational weight gain intervention in military personnel and other TRICARE beneficiaries. Issue 10 (30th August 2022) - Estevez Burns, Rosemary; Hare, Marion E.; Andres, Aline; Klesges, Robert C.; Talcott, Gerald Wayne; LeRoy, Karen; Little, Melissa A.; Hyrshko‐Mullen, Ann; Waters, Teresa M.; Harvey, Jean R.; Bursac, Zoran; Krukowski, Rebecca A.
Abstract: Objective: Despite military fitness regulations, women in the military frequently experience overweight/obesity, excessive gestational weight gain (GWG), and the postpartum implications. This interim analysis of the Moms Fit 2 Fight study examines GWG outcomes among active‐duty personnel and other TRICARE beneficiaries who received a stepped‐care GWG intervention compared with those who did not receive a GWG intervention. Method: Participants ( N  = 430; 32% identified with an underrepresented racial group, 47% were active duty) were randomized to receive a GWG intervention or the comparison condition, which did not receive a GWG intervention. Results: Retention was 88% at 32 to 36 weeks' gestation. Participants who received the GWG intervention gained less weight compared with those who did not (mean [SD] = 10.38 [4.58] vs. 11.80 [4.87] kg, p  = 0.0056). Participants who received the intervention were less likely to have excessive GWG compared with those who did not (54.6% vs. 66.7%, p  = 0.0241). The intervention effects were significant for participants who identified as White, but not for those of other racial identities. There were no significant differences between the conditions in maternal/neonatal outcomes. Conclusions: The intervention successfully reduced excessive GWG, particularly among participants who identified as White. Should this intervention be found cost‐effective, it may be sustainably integrated throughout the military prenatal care system.